Creation of Money in a Full Reserve Banking System and the Separation of Money from Interest – Presentation of the Balance Sheets of the Central Bank and Commercial Banks in Bosnia and Herzegovina - Adisa Omerbegović Arapović (Društvene i Humanističke Studije)
This paper evaluates the impact of a paradigm shift in the monetary system by introducing a model of full reserve banking, focusing on the outcome of separating the generation of money from interest, which can only be achieved by abolishing the system of creating money through debt creation in the banking system. The main thesis argues that the current system, in which private commercial banks create money by issuing loans, results in deposits that mix savings achieved through economic activity with newly created money, leading to economic inefficiency and potential instability because debt and interest are always greater than the economic value created. The 100% sovereign money system corrects this by ensuring that only the central bank has the authority to create money, simplifying the financial landscape and restoring money to its rightful status as a public good and stable unit of measure. The study uses a comparative analysis between the current banking system with fractional reserves and the proposed banking system with 100% sovereign money, which is entirely reserve money. Balance sheet modeling demonstrates the impact of segregating investment and deposit accounts on the books of banks and the central bank. The methodology includes a hypothetical presentation of the balance sheet under the new system, emphasizing the accounting separation of “deposit” and “investment” accounts to end the creation of money by private commercial banks. The balance sheet analysis indicates that adopting a 100% sovereign money system requires state intervention through state deposits into the banking system to achieve the desired level of credit activity.